Professional Efficiency of Medical Staff in E-Health Care: The Role of Digital Competencies - o'g'li, Naimov Dilshod Qayim (Journal of Science in Medicine and Life, 2024)
E-health is defined as the use of information and communication technologies (ICT) in health care to improve the efficiency and effectiveness of health care management and delivery [1]. E-health improves health surveillance, healthcare system management, healthcare decision-making, and standardizes the exchange of medical information; and promotes equity in health care delivery. E-health has the potential to improve access to healthcare and can effectively reduce professional isolation and improve retention of healthcare professionals in resource-limited settings [2].